Detection of changes in synaptic density in amyotrophic lateral sclerosis patients using 18F‐SynVesT‐1 positron emission tomography. (6th July 2022) - Tang, Yongxiang; Liu, Pan; Li, Wanzhen; Liu, Zhen; Zhou, Ming; Li, Jian; Yuan, Yanchun; Fang, Liangjuan; Wang, Mengli; Shen, Lu; Huang, Yiyun; Tang, Beisha; et al.
Abstract: Background and purpose: Synaptic loss is well established as the major correlate of characteristic and consistent pathology in amyotrophic lateral sclerosis (ALS). We aimed to assess the possible discriminant diagnostic value of 18 F‐SynVesT‐1 positron emission tomography (PET) as a marker of ALS pathology and investigate whether specific synaptic density signatures are present in ALS with different subtypes. Methods: Twenty‐one patients with ALS and 25 healthy controls (HCs) were recruited. All participants underwent 18 F‐SynVesT‐1‐PET. Synaptic density between ALS and HCs and between different ALS subgroups were compared. Correlation between synaptic density and clinical features in ALS was also analyzed. Results: Low uptake distribution was found in the group comprising 21 ALS patients as compared with HCs in the right temporal lobe and the bilateral inferior frontal gyrus, anterior cingulate, and hippocampus–insula region. We also found low uptake in the bilateral superior temporal gyrus, hippocampus–insula, anterior cingulate, and left inferior frontal gyrus in ALS patients with cognitive impairment compared to HCs. Furthermore, compared to spinal onset ALS, bulbar onset ALS showed low uptake in the bilateral cingulate gyrus and high uptake in the bilateral superior temporal gyrus and left occipital lobe. No significant result was found in correlation analysis. Conclusions: This approach may provide a direct measure of synaptic density, and it therefore might represent a potentially useful biomarker for ALS diagnosis, as well as for estimating the cognitive decline and site of onset in ALS. 18 F‐SynVesT‐1‐PET is presently not justified as a routine investigation to detect evidence of brain dysfunction leading to progression in ALS. Abstract : This approach may provide a direct measure of synaptic density, and it therefore might represent a potentially useful biomarker for amyotrophic lateral sclerosis (ALS) diagnosis, as well as for estimating the cognitive decline and site of onset in ALS.